2013
DOI: 10.3109/14756366.2013.845820
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of quinazoline derivatives: search for hybrid molecule as diuretic and antihypertensive agents

Abstract: To explore the pharmacological and structure-activity relationship of a series of N-substituted-(4-oxo-2-substituted-phenylquinazolin-3-(4H)-yl), substituted benzene sulfonamide derivatives (1-25) were synthesized from substituted anthranilic acids derived amino quinazolines and substituted benzene sulphonamides. All the synthesized compounds were evaluated for their diuretic (by Lipschitz et al. method), antihypertensive activity by non-invasive blood pressure (NIBP) using the tail-cuff method and anti-diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Javaid et al [95] reported a quinazolinone derivative (111; Figure 15) with IC50 value of 0.3 ± 0.01 μM which is about 2800-fold more potent than acarbose reference standard drug. Rahman et al [96] synthesized a series of hybrid compounds consisting of N-substituted-(4-oxo-2-substituted-phenylquinazolin-3-(4H)-yl) substituted benzene sulfonamide derivatives. From this series, compounds (112-116; Figure 15) explored significant antidiabetic activity.…”
Section: α-Glucosidase Inhibitor Activitymentioning
confidence: 99%
“…Javaid et al [95] reported a quinazolinone derivative (111; Figure 15) with IC50 value of 0.3 ± 0.01 μM which is about 2800-fold more potent than acarbose reference standard drug. Rahman et al [96] synthesized a series of hybrid compounds consisting of N-substituted-(4-oxo-2-substituted-phenylquinazolin-3-(4H)-yl) substituted benzene sulfonamide derivatives. From this series, compounds (112-116; Figure 15) explored significant antidiabetic activity.…”
Section: α-Glucosidase Inhibitor Activitymentioning
confidence: 99%
“…The 2,3-dihydroquinazolin-4(1H)-ones (2,3-DHQs) are fused heterocyclic compounds which exist in natural products such as luotonins A, B, E, and F [13], tryptanthrin [14], and rutaecarpine [15]. 2,3-DHQs possess a broad range of pharmacological properties such as anti-cancer [16,17], antidepressant [18], antidiabetic [19], antifungal [20], antihypertensive [21,22], analgesic, anti-inflammatory [23,24], antibacterial [25], antioxidant [26], and antiviral [27] activities; they also act as bronchodilator [28], centrally acting muscle relaxant [29], diuretic [30], sedative, and hypnotic [31] agents (Figure 1). Quinazoline derivatives were also reported as bactericides [32], fungicides [33], and insecticides [34].…”
Section: Introductionmentioning
confidence: 99%
“…Such derivatives, 2- sec -amino-3 H -quinazolin-4-ones, displayed a significant reduction in blood glucose level in streptozotocin and sucrose-loaded rat models [ 6 ] as well as 1-thioxo-1,2,7,8,9,10-hexahydro-3 H -pyrimido[1,6- a ]quinazolin-3-one [ 7 ]. Also, N -substituted-(4-oxo-2-substituted-phenylquinazolin-3-(4 H )-yl), namely N -[7-chloro-2-(4-methoxyphenyl)-4-oxoquin-azolin-3(4 H )-yl]-4 nitrobenzenesulfonamide, exhibited high antidiabetic potential [ 8 ]. In addition, N -4(substituted phenyl)-5-{[(2-phenylquinazolin-4-yl)-oxy]-methyl}-1,3,4-thiadiazol-2-amine derivatives according to docking glide score showed a high potency with regards to hypoglycemic activity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%